Community-based intervention to reduce stigma for children with disabilities in Lusaka, Zambia: a pilot. Issue 11 (22nd May 2022) - Hearst, Mary O.; Adelli, Rakesh; Hepperlen, Renee; Biggs, Jennifer; DeGracia, Donna; Ngulube, Esther; Maluskiku-Mwewa, Batuke; Johnson, Dana E.; Rabaey, Paula
Abstract: Purpose: This pilot intervention aims to reduce stigma towards children with disabilities living in family-based care. Materials and methods: Kusamala + is a pre-post evaluation of a pilot community-based intervention in two low-income compounds in Lusaka, Zambia. Door-to-door canvassing and community referrals were used to identify and enroll children with disabilities. Parents/guardians and community members completed surveys regarding stigma and support. Health professionals supervised, trained, and provided ongoing support for 2–3 community caregivers (CCGs). CCG's provided home-based education, referrals, playgroups, and social support for 20–25 families each. Community events were held at health facilities, churches and community spaces to reduce community-level stigma towards children with disabilities. Results: Staff identified 632 children with disabilities. Staff completed over 4500 home visits, 288 children joined playgroups, made 775 referrals, and over 23, 000 attended community sensitization events. Longitudinal data was available for 129 families with a child with a disability. Over one year, families and community members reported less perceived rejection by family and peers but less agreement that children with disabilities should be treated the same as other children. Conclusion: Kusamala + was a feasible, acceptable and broad reach with limited program impact. Future work will incorporate lessons learned with a focus on sustainability and scalability. Implications for rehabilitation: Children with disability are often hidden and isolated in low- and middle-income countries (LMIC), particularly in low-resource communities. Stigma towards children with disabilities continues in LMIC and further reduces that child's ability to engage fully in social and civic life. Community- and home-based programming is a feasible and acceptable approach to engaging with community and families with a child with a disability. The identification and referral of additional children with disabilities to physiotherapy and other government services can provide additional strain on already limited resources. Once a pilot program is deemed acceptable and feasible, any further design planning must include considerations for sustainability and scalability. System strengthening is a key component of sustainability and scalability to ensure success in planning, implementation, monitoring and evaluation.